Global mantle structure from multi-frequency tomography using P, PP and P-diffracted waves - Hosseini, K; Sigloch, K; Tsekhmistrenko, M; Zaheri, A; Nissen-Meyer, T; Igel, H (Oxford University Press, 2019)
In global-scale seismic tomography, teleseismic P and PP waves mainly constrain structures in the upper two thirds of the mantle, whereas core-diffracted waves (Pdiff) constrain the lower third. This study is the first to invert a very large data set of Pdiff waves, up to the highest possible frequencies. This results in tomographic resolution matching and exceeding that of global S-wave tomographies, which have long been the models of choice for interpreting lowermost mantle structure.